Goosebumps: The Barking Ghost - Stine, R L (Scholastic Ltd, 1995)
The barking ghost takes place in a new home, in the middle of the forest, that Coopers parents buy. Cooper does not want to move into that house. Cooper meets a girl named fergi and they become good friends. There are two ghost dogs in the forest that want to get into Cooper and fergi's bodies. The dogs try to get into their bodies so that they can have a human life like they used to have. A lot of things happen to Fergi and Cooper. Until the dogs get what they want. Coopers mom notices a difference in Cooper but she doesn't Know what happened. If you want to find out what happens to Cooper and Fergi then read this book.
Keywords: Horror & Ghost Stories; Juvenile Fiction